KEBEBASAN PERS DAN SENSOR REPRESIF - Murani, Asnawi (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
Press,  undeniably, has a very strong  power to change the society. The moving  force comes  from the information it carries. Therefore, both  the government  and other parties should take it into considerations. In anticipating press abuse, the government  applies preventive and repressive censorship as a controlling mechanism. Besides, freedom of expression as a form of freedom of the press starts form the human rights. People have their rights to express their feeling  as  they  tike.  However, there should  be  balanced  information  that assumes responsibility as stated in the draft of Convention on  the Freedom of Information. This leads to create the rules of the game between  the press and the government  in developing the society.